Validity and Reliability of the Adoption Questionnaire of Agricultural Mechanization in the Food Estate Area of Central Kalimantan Indonesia - Anto, Astri; Sugiyanto, Sugiyanto; Yuliati, Yayuk; Kustanti, Asihing (International Journal of Science, Technology & Management, 2023)
The use of agricultural mechanization has greatly contributed to the modernization of agricultural systems in many developing countries, including Indonesia. One implementation of agricultural modernization is the application of agricultural mechanization in the food estate program in Central Kalimantan, Indonesia. The adoption of agricultural mechanization is a determinant of the implementation of agricultural mechanization in the food estate area. However, the problem is that the speed of adoption of agricultural mechanization by farmers in the food estate area is still varied. The purpose of this research is to test the validity and reliability of the questionnaire in the study of agricultural mechanization adoption to support agricultural modernization in the food estate area of Central Kalimantan. This research was conducted using a quantitative research design with rice farmers who received the food estate program as the unit of analysis in the Pulang Pisau and Kapuas districts, Central Kalimantan. Data was collected purposively from 42 rice farmers in the food estate area by providing a questionnaire containing five indicators of agricultural mechanization adoption. The results showed that the questionnaires were valid and reliable with correlation values (Pearson Correlation) for the five indicators of awareness, interest, evaluation, trial, and adoption with fifteen questions showing the value of R count > R table and declared valid. While Cronbach's Alpha value is 0.794-0.951. Meanwhile, Cronbach's Alpha value was 0.794-0.951. Based on the discussion, it can be concluded that the questionnaire is valid and reliable.